The effect of the cluster learning strategy on the achievement of the students of the Institute of Fine Arts in subject of Artistic taste (Journal of the College of Basic Education, 2024)
The study aimed to identify the effect of the cluster learning strategy on the achievement of the students of the Institute of Fine Arts in the subject of Artistic taste, and some zero hypotheses were derived, including: (There are no statistically significant differences at the level of significance (0.05) between the mean ranks of the students of the experimental group and the mean ranks of the ranks of the experimental group. The students of the control group on the cognitive test of art history subject. To achieve the goal of the research, the researcher used the experimental approach and the experimental design with two equal groups with a pre and post test for the subject of Art History due to its suitability to the research procedures. The research sample consisted of (30) female students distributed equally between the two research groups, and study plans were built on some of the vocabulary of art history, namely: (Baroque arts, and Rococo arts) and according to the cluster learning strategy. The research tool consisted of a knowledge achievement test for the subject Artistic taste for the fourth stage, and to reach the results of the research, the researcher used the statistical bag (spss).The most important results of the study showed:The cluster learning strategy contributes to clarifying the role of the teacher as an organizer of environmental conditions that facilitate learning.There is a very high difference between the two responses, before and after, on the achievement test of the students of the Institute of Fine Arts in the subject of Artistic taste. Based on the results of the study, the researcher recommended several recommendations, including:Adopting the cluster learning strategy in teaching art history, because it has proven effective in creating experiences and positive attitudes towards knowledge content.Paying attention to modern teaching methods, which make the learner the focus of the educational process, and directing the teaching staff to move away from the traditional methods in the education process, and keep pace with the great development in the emergence of teaching methods that are commensurate with the modern era.As a complement to the current research, the researcher suggested several proposals, including:Conducting a similar study to find out the impact of the cluster learning strategy on developing the skillful performance of some art education subjects.